Suicide Risk Assessment and Risk Formulation Part I: A Focus on Suicide Ideation in Assessing Suicide Risk. Issue 4 (9th January 2014) - Silverman, Morton M.; Berman, Alan L.
<x xml:space="preserve">Abstract</x> The main procedure used by clinicians to determine whether an individual may be at risk of suicidal behaviors is the suicide risk assessment (SRA). The purpose of the SRA is to identify risk and protective factors that then provide the data for the formulation of suicide risk. The suicide risk formulation (SRF) assigns a level of suicide risk that ideally leads to triage and treatment deemed appropriate for that level of risk. Some of the problems with the SRA are explored here, with an emphasis on addressing the over reliance on communicated suicide ideation, and recommendations are made for improvements. Part II of this article (Berman & Silverman, 2013, also appears in this issue of STLB) examines the process of an SRF and, similarly, makes recommendations to improve clinical practice toward the desired end of saving lives.